Analysis of determinants of work accidents in fabrication workers in the steel structure workshop area at PT X in 2024 - Sukriyadi, Sukriyadi; Ariyanto, Januar; Srisantyorini, Triana; Putri, Aragar (Institute of Computer Science (IOCS), 2025)
Accidents are unexpected, undesirable events and can cause material and life losses. Accident prevention must be carried out based on the control hierarchy and the root causes of the accident. Purpose: The aim of this research is to know the determinants of work accidents among fabrication workers in the steel structure workshop area at PT X in 2024. The research method uses a cross sectional design. The sample was 58 respondents from a population of 112 workers at PT Data were collected using a questionnaire. The data was tested using the chi square test. The research results showed that of 58 respondents, 26 (44.8%) had experienced work accidents. Variables are age (P=0.126), education level (P=1.000), length of service (P= 0.126), length of work (p=0.029; OR 11.143), OHS knowledge (P=0.290), use of PPE (P=0.003; OR=5.971). There is a significant relationship between length of work and use of PPE and the incidence of work accidents among fabrication workers in the steel structure workshop area. The conclusion is that there is a relationship between compliance with the use of PPE and length of work with work accidents, while the factors age, education, length of service, OHS knowledge have no relationship with the incidence of work accidents. Suggestions are to regulate employee working hours so that there is no overtime in work progress and to increase compliance with the use of PPE for fabrication workers in the steel structure workshop area of ​​PT.